Shakedown analysis and design of flexible road pavements under moving surface loads - Wang, Juan (2011)
Flexible road pavements often fail due to excessive rutting. as a result of cumulative vertical permanent deformation under repeated traffic loads. The currently used analytical approach to flexible pavement design evaluates the pavement life in terms of critical elastic strain at the top of the subgrade. Hence, the plastic pavement behaviour is not properly considered. Shakedown analysis can take into account the material plasticity and guarantee structure stability under repeated loads. It provides a more rational design criterion for flexible road pavements.